2021
DOI: 10.1002/aur.2482
|View full text |Cite
|
Sign up to set email alerts
|

Prediction in Autism Spectrum Disorder: A Systematic Review of Empirical Evidence

Abstract: According to a recent influential proposal, several phenotypic features of autism spectrum disorder (ASD) may be accounted for by differences in predictive skills between individuals with ASD and neurotypical individuals. In this systematic review, we describe results from 47 studies that have empirically tested this hypothesis. We assess the results based on two observable aspects of prediction: learning a pairing between an antecedent and a consequence and responding to an antecedent in a predictive manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
104
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 103 publications
(231 reference statements)
12
104
2
Order By: Relevance
“…Since the formulations of these hypotheses, several studies attempted to test them more directly. A recent systematic review evidenced some differences between ASD and NT individuals in predictive learning and predictive responses [ 16 ]. They found that most of the studies investigating the predictability of repeated stimuli showed reduced habitation in ASD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since the formulations of these hypotheses, several studies attempted to test them more directly. A recent systematic review evidenced some differences between ASD and NT individuals in predictive learning and predictive responses [ 16 ]. They found that most of the studies investigating the predictability of repeated stimuli showed reduced habitation in ASD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proposed differences in predictive processing 22 align with a range of autism-related sensorimotor atypicalities, including: impaired movement planning 23 , 24 , reduced anticipatory motor adjustments 7 , 25 , suboptimal movement initiation kinematics 5 , 8 , slower error-based saccade adaptation 26 , and atypical gaze fixation behaviours 27 . However, prediction-related difficulties only emerge under some task conditions (see review 28 ), with autistic people demonstrating intact visual motion prediction 29 , anticipatory lifting forces 30 , and non-social ocular tracking abilities 31 . These inconsistent findings undermine proposals that prior expectations are generically attenuated in autism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have illustrated abnormalities in predictive abilities in autistic individuals outside the domains of language (see Cannon et al, 2021 , for a recent review of empirical evidence). Neuroimaging and eye-tracking studies using tasks in which participants are presented with predictable repetitive stimuli that are infrequently interrupted by an unpredictable deviant stimulus found that autistic individuals showed an altered response compared to neurotypical controls (Jeste et al, 2015 ; Balsters et al, 2017 ; Lawson et al, 2017 ; Goris et al, 2018 ).…”
Section: Recent Developmentsmentioning
confidence: 99%